A REVIEW OF THE USE OF INTERACTIONAL METADISCOURSE MARKERS OF HEDGES AND BOOSTERS IN ACADEMIC WRITING - Mizad, Meizareena; Hashim, Siti Afifah (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
In academic writing, managing authorial stance is crucial in developing authority and engaging readers. However, undergraduates as novice writers are not aware that metadiscourse markers may help them to manage stance in writing. As a result, they tend to misuse these linguistic features and generate imprecise assertive claims which affect the tone and precision. This paper examines the use of interactional metadiscourse markers of hedges and boosters in academic writing by exploring the gaps in the literature, challenges, and future recommendations. Hedges, such as might, possible, and boosters, such as definitely, in fact, are crucial rhetorical tools for expressing degrees of certainty. Although Hyland’s Interpersonal Model (2005) has provided insights into metadiscourse use across genres, the use of metadiscourse in academic writing class instruction remains limited. Hence, this narrative review aims to examine the use of hedges and boosters in academic writing, focusing on their distribution and rhetorical functions, and explores their pedagogical implications for academic writing instruction, particularly in tertiary education contexts. The review presents findings on discourse analysis to highlight how these features contribute to stance-taking, argumentation, and reader engagement. Finally, this review highlights the need to integrate explicit instruction on hedges and boosters in writing pedagogy to maintain rhetorical competence and academic literacy among student writers.